(untitled) (Global Journal of Human-Social Science, 2018)
Employing travel writings and juridical documentation created during the colonial period in Mexico, this article offers an analysis of the transfer of plants and animals from the Old World to North America and their effects, with a particular focus on Mexico City from the sixteenth to eighteenth centuries. The aim of this paper is to highlight the role of the orchards and gardens associated with the Discalced Carlemite Order’s convents as a key site that allowed for the adaptability of different European and Asiatic plants in Mexican lands.